Reading the Costanzo Obligation in the Light of the Pure Theory of Law - Fabian, Ewa (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
In this article, I discuss the obligations of administrative authorities in European Union (EU) member states applying EU law from the perspective of some of the views presented by Hans Kelsen in his Pure Theory of Law. Reference is made particularly to the case of Fratelli Costanzo (Judgment of the Court of 22 June 1989, 103/88, Fratelli Costanzo SpA v Comune di Milano, ECLI:EU:C:1989:256). The judgment established a rule requiring national administrative authorities, in certain matters, to refuse the application of the provisions of national law which are incompatible with EU law (this rule is also known as the Costanzo Obligation). It is sometimes claimed, however, that administrative bodies are not expected to disregard the binding provisions of national law which are unambiguous in their content, and interpret them in a pro-EU manner, filling thus established gaps with domestic laws of their choosing. It is claimed that such interpretation may only be performed by the national judiciary but not by the administrative branch. In this article, I oppose this position, referring to the views expressed by Hans Kelsen, in three separate arguments. I present these arguments pointing out that the non-application of the principles of EU law by an administrative branch may deprive the applicant of the right to judicial protection.